PERIOD OF INTENSE VEGETATION IN POLAND IN THE YEARS 1966–2015 - Tomczyk, Arkadiusz M.; Szyga–Pluta, Katarzyna (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The purpose of this paper was to determine long-range and spatial variability of the start and end dates of a period of intense vegetation in Poland in 1966–2015. The article is based on average monthly air temperature values acquired for 20 Polish stations for 1966–2015, made available by the Institute of Meteorology and Water Management – the National Research Institute. Based on the obtained data, the dates of the beginning and end of the intense vegetation period were determined. In this study, the intense vegetation period was defined as one with an average daily air temperature ≥10°C. The mathematical formulas proposed by Gumiński (1948) were used to determine the dates of the beginning and end of the period. A period of intense vegetation in Poland in the years 1966–2015 has extended. The dates of the beginning of the period of intense vegetation changed in the latitudinal system from the south to the north while the intensity of changes in the date of the beginning in the studied area was characterized by longitudinal distribution – the most prominent in the west of Poland. The end of the intense vegetation period occurs earliest in the north-east of Poland, and latest in the west and the south. The end date changes were less significant than the start date changes. The length of the intense vegetation period ranges from the north-east to the south-west of Poland, and the most dramatic changes occurred in the west and the south-east of Poland.